PUnet: A robust framework for phase unwrapping in interferometric SAR - Liu, Boyu; Wu, Lingda; Song, Xiaorui; Hao, Hongxing; Zou, Ling; Lu, Yu (Frontiers in Environmental Science, 2023)
Synthetic Aperture Radar (SAR) Interferometry (InSAR) has grown significantly over the past few decades, which were mainly used in remote sensing applications,. Most InSAR applications (e.g., terrain mapping and monitoring) utilized a key technique called phase unwrapping (PU). Phase unwrapping obtained the absolute phase from the wrapped phase for the subsequent application. However, the collected wrapped phase inevitably contains noise due to the influence of factors such as atmosphere and temperature in the InSAR acquisition stage. This noise made it challenging to obtain the absolute phase from the wrapped phase. This study proposed a deep learning framework (PUnet) for phase unwrapping form InSAR data. PUnet was a robust framework usingU-net as the basic structure combined with an attention mechanism and positional encoding, facilitating accurate phase unwrapping from the wrapped phase. Through comparative experiments with typical phase unwrapping algorithms, we demonstrated that PUnet could obtain absolute phases with high accuracy and robustness than…from the wrapped phase under various levels of noise.